Exploring Students’ Perceptions of Small WhatsApp-Based Instruction versus Traditional Group-Driven Reading Methods - Nirwanto Maruf (Jurnal Ilmiah Jendela Pendidikan, 2022)
This study aimed to investigate the impact of Small WhatsApp-based instruction versus Traditional Group-Driven Reading methods on students’ perceptions of engagement, motivation, and satisfaction. The participants were randomly assigned to the Small WhatsApp group and the traditional group-driven reading group. The results of the questionnaires revealed that the students in the Small WhatsApp group had higher levels of engagement, motivation, and satisfaction with the instruction compared to those in the traditional group-driven reading group. Specifically, the results showed that the students in the Small WhatsApp group reported higher level of engagement, motivation, and satisfaction with an average score respectively of 4.2, 4.1 and 4.3 on a 5-point Likert scale, in contrast, the students in the traditional group-driven reading group reported an average score of 3.6, 3.5 and 3.8 on the engagement, motivation, and satisfaction scale. These results indicate that students who received instruction using Small WhatsApp had more positive perceptions of their instruction in terms of engagement, motivation, and satisfaction. The results of the study suggest that the use of Small WhatsApp can be effective tool for promoting student engagement and motivation in the classroom. Nevertheless, this study suggests for future researches should investigate the use of other forms of technology-assisted instruction in reading instruction.